1998
DOI: 10.1002/(sici)1521-3773(19981002)37:18<2490::aid-anie2490>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Ruthenium Catalysts for Olefin Metathesis

Abstract: The different nature of carbene ligands is clearly demonstrated by the first ruthenium-based complexes 1, which contain both alkylidene and N-heterocyclic carbene moieties. The latter exhibit a pronounced Lewis base behavior. Moreover, this difference forms the basis of the high catalytic activities of these compounds in olefin metathesis reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
73
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 570 publications
(80 citation statements)
references
References 1 publication
7
73
0
Order By: Relevance
“…Since the pioneering reports on the utilisation of N -heterocyclic carbenes (NHC) as co-ligands in ruthenium-based carbene complexes for olefin metathesis [13] in the late nineties of the last century, olefin metathesis has become a powerful carbon-carbon double-bond-forming tool presenting unique synthetic opportunities [4]. Developments in this area can be attributed to a steady and competitive research, focused on improving activity, selectivity and functional group tolerance of the catalysts by changing the leaving co-ligand [4–5], by using tailored carbene ligands [57], by introducing new NHC ligands [5,89], or by variation of the anionic co-ligands [5] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering reports on the utilisation of N -heterocyclic carbenes (NHC) as co-ligands in ruthenium-based carbene complexes for olefin metathesis [13] in the late nineties of the last century, olefin metathesis has become a powerful carbon-carbon double-bond-forming tool presenting unique synthetic opportunities [4]. Developments in this area can be attributed to a steady and competitive research, focused on improving activity, selectivity and functional group tolerance of the catalysts by changing the leaving co-ligand [4–5], by using tailored carbene ligands [57], by introducing new NHC ligands [5,89], or by variation of the anionic co-ligands [5] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed complexes bearing both a phosphane and a NHC ligand, so-called 2 nd generation catalysts, typically display better thermal stability and activities compared to 1 st generation catalysts [910]. Key to the success and research activity involving 2 nd generation catalysts has been the wide selection of NHCs available [1112].…”
Section: Introductionmentioning
confidence: 99%
“…Although NHC-metal complexes have been known particularly as catalysts [12,15,[21][22][23][24][25][26][27] for various chemical transformations, later discoveries showed that these complexes can be used in medical applications [84][85][86][87][88][89]. Developments of NHC-metal complexes as anticancer agents have been comprehensively reviewed in the recent past by Deng et al [90] and Bhagat et al [91].…”
Section: Biological Activity Of Nhc-metal Complexesmentioning
confidence: 99%
“…Reduced cross resistance to cisplatin, decreased toxicity and high specificity of many new mononuclear, dinuclear and multinuclear palladium complexes have been developed. Palladium complexes might materialize a concept of tumor targeting which would result in drugs with other spectrum of activity 103 -HCT 119 [116] 104 26.5 HCT 119 [116] 105 6.6 HCT 119 [116] t-Bu NH future science group N-heterocyclic carbene metal complexes as bio-organometallic antimicrobial & anticancer drugs Review and lack of cross-resistance as compared with platinum drugs [30,103,141].…”
Section: Antimicrobial and Antitumor Activities Of Nhc-palladium Complexesmentioning
confidence: 99%
See 1 more Smart Citation